CHALLENGES AND SOLUTIONS TEACHERS ENCOUNTER WHILE INTEGRATING TECHNOLOGY IN THE CLASSROOM - Sultanova Barchinoy Davronovna (PEDAGOGS, 2024)
Abstract: Teachers face several challenges when integrating technology into the classroom. These challenges include a lack of technology media facilities, slow internet connections, and a lack of teacher skills in mastering technology. Additionally, teachers may face challenges such as a lack of competence, deficient teaching materials, and inadequate digital teaching skills. Other barriers include a lack of resources, time, access, and technical support. Furthermore, teachers may encounter obstacles such as a lack of access to ICT resources, lack of access to the internet inside the classroom, lack of training, and insufficient technical support. These challenges can hinder the effective integration of technology in the classroom and impact the overall learning experience for students.